Differential role of HLA-A and HLA-B, C expression levels as prognostic markers in colon and rectal cancer. Issue 3 (11th March 2022) - Michelakos, Theodoros; Kontos, Filippos; Kurokawa, Tomohiro; Cai, Lei; Sadagopan, Ananthan; Krijgsman, Danielle; Weichert, Wilko; Durrant, Lindy G; Kuppen, Peter J K; R Ferrone, Cristina; Ferrone, Soldano
Abstract : Purpose: The association of human leucocyte antigen (HLA) class I expression levels with the clinical course of many malignancies reflects their crucial role in the recognition and elimination of malignant cells by cognate T cells and NK cells. In colorectal cancer, results regarding this association are conflicting. The potential pathogenetic and therapeutic implications of this association prompted us to perform a large patient-level pooled analysis assessing the role of the expression level of HLA class I loci gene products in colon and rectal cancer. Experimental design: Included studies provided patient-level data on HLA class I expression levels determined by immunohistochemistry on surgical specimens. Expression levels of the HLA class I loci gene products (HLA-A, HLA-B/C) were correlated with common genetic events and survival. Results: Data from 5 studies including 2863 patients were used. In the 1620 colon cancer patients, lower HLA-A, HLA-B/C and total HLA class I expression levels were associated with microsatellite instability (p=0.044, p=0.008 and p=0.022, respectively), higher frequency of BRAF mutations (p<0.001, p=0.021 and p<0.001, respectively) and lower frequency of KRAS mutations (p=0.001, ns and p=0.002, respectively). In the 1243 rectal cancer patients, HLA-A expression was higher in tumors treated with neoadjuvant radiation (p=0.024). High HLA-B/C, but not HLA-A, expression level was an independent predictor of favorable overall survival in colon (p=0.006) and rectal (p<0.001) cancer. Conclusions: T-cells and HLA-B/C antigens, rather than NK cells and HLA-A antigens, likely play an important role in controlling colon/rectal cancer growth. Colon/rectal cancer patients may benefit from strategies that upregulate HLA-B/C and trigger or enhance T cell immunity.